Stem Education In Primary School - Nilufar Otojanova (Genius Journals, 2025)
The article explores the role of innovative educational technologies, particularly the STEM education concept (Science, Technology, Engineering, Mathematics), in preparing specialists capable of meeting the challenges of modern society. It addresses the need to enhance human competitiveness amidst rapid technological progress and competition with artificial intelligence. Special attention is given to the integration of STEM approaches into the educational process, including interdisciplinary and practiceoriented methods that foster the development of critical thinking, creativity, and engineering competencies. Examples of STEM education implementation in Uzbekistan, aligned with national programs, are provided, alongside an analysis of global experiences and trends in this field. The article emphasizes the importance of STEM in shaping a new generation of professionals ready for innovative activities in the context of globalization.
Keywords: STEM education; innovative learning technologies; competitiveness; interdisciplinary approach